Verbal humour in Pataclaun: the phenomenon of paronomasy - Mendoza Villanueva, Mariana (2018)
The article contains a compilation of some dialogues presented in the Pataclaun program (1997-1999) that allow the visualization and explanation of the phenomenon of paronomasia, defined by López (2005) as a language game that involves linguistic phenomena such as polysemy, homonymy and resegmentation. Paronomasia is configured through various linguistic phenomena, such as polysemy and homonymy. From the above, the article concludes that paronomasia is an applicable concept for a study of the characteristics of verbal humor in the Pataclaun program.